Pengaruh Kandungan Senyawa pada Ekstrak Daun Ketapang n-Heksan, Etil Asetat, Metanol dan Campuran Terhadap Nilai Efisiensi Dye Sensitized Solar Cell (DSSC) - Aisyah Aisyah; Kurnia Arini Putri; Suriani Suriani; Iswadi Iswadi (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2017)
The needs of electrical energy that increase year by year cause electrical energy crisis. Alternative energy sources which are potential to be developed as a substitute of fossil fuels are organic solar cells or DSSC (Dye Sensitized Solar Cell). The purpose of this study is to determine the value of efficiency resulting from Ketapang leaf extract and to determine the effect of compound content in Ketapang leaf extract toward the value of DSSC efficiency. This study investigate the efficiency value of the DSSC which are senzitized by the N-hexane, ethyl acetate, methanol extract of the Ketapang leaf and the mixture extract. The compounds from each axtract are characterized used UV-Vis and FTIR. The measurement results of the efficiency value from n-hexane of Ketapang leaf extract, ethyl acetate, methanol and the mixture were respectively 0.0051%, 0.09%, 0.12% and 0.22%. The results of UV-Vis characterization with maximum wavelength were respectively 667 nm, 665.9 nm, 665.9 nm and 209 nm. The FTIR identified an auxchrome group such as -OH, C-N, -NH, and C-O as well as chromophore groups such as C=O and C=C. These data support that the existence of flavonoid and alcaloid compound in the mixture extract generate significant efficiency value.